Enzymatic Synthesis of Butyl Laurate by Immobilized Rhizopus Oryzae Lipase onto Silica Aerogel: Optimization by Response Surface Methodology - Kharrat, Nadia; Aissa, Imen; Kamoun, Amel; Ben Ali, Yassine; Chaâbouni-Karra, Maha; Gargouri, Youssef (Current Chemical Biology, 2013)
Given the importance of butyl laurate in various industrial fields, its production by enzymatic catalysis has received greater interest. Butyl laurate was successfully synthesised by the esterification of lauric acid with butanol. This reaction was catalyzed by Rhizopus oryzae lipase immobilized onto silica aerogel in organic media. Response surface methodology was applied in order to approximate the effect of the butanol/ lauric acid molar ratio (1.2-5 mol/mol), the amount of lipase (100-700 IU) and the volume of hexane (3-9 mL) on the butyl laurate lipase-catalyzed esterification yield through an empirical model. Results clearly indicated that the lipase amount was the main factor influencing the synthesis yield. This yield increased with the lipase amount and decreased with the molar ratio of butanol/ lauric acid and the volume of hexane. The selected optimal conditions for synthesis were: a butanol/ lauric acid molar ratio of 1.2, a lipase amount of 550 IU and an hexane volume of 3 mL. The application of these optimized conditions led to a butyl laurate yield of 90.5%. The immobilized lipase was successfully reused for 26 cycles without a significant decrease of the conversion yield on butyl laurate. These results confirm the idea that employing Rhizopus oryzae lipase immobilized onto silica aerogel for a wide range of esterification reactions is feasible.
Keywords: Immobilized Rhizopus oryzae lipase